PIER PERFORMANCE LEVEL OF JAKARTA-BANDUNG HIGH SPEED RAILWAY WITH ISOLATOR UNDER EARTHQUAKE LOADS USING TIME HISTORY ANALYSIS - Amirah Zakiyyah; Aris Aryanto; Bayu Wintoro (Jurnal Ilmiah Teknik Sipil, 2024)
This study analyzes the performance level of a typical pier structure on the Jakarta-Bandung High-Speed Railway (HSR) bridge located in the Bandung area, focusing on the effects of seismic loads. The structure utilizes double spherical bearings (isolators), and its performance is compared with a similar structure without isolators to evaluate the isolators’ effectiveness under design-level earthquakes. A Non-linear Time History Analysis (NLTHA) was conducted using 11 pairs of ground motion records. These motions were scaled to match the target response spectrum for Bandung using amplitude scaling in the DeepSoil program. Structural analysis was carried out using Midas Civil to determine the seismic performance levels of the piers Additionally, pier displacements were examined to further assess isolator performance. The results show that the structure equipped with isolators maintained a Fully Operational (FO) performance level, indicating minimal damage and full functionality after the earthquake. In contrast, the structure without isolators surpassed the elastic range but remained within the Immediate Occupancy (IO) performance level, suggesting minor damage but continued usability. These findings confirm that the use of isolators significantly enhances the seismic resilience of bridge piers in high-speed railway.